Changing Climate in a Mountain Sub-watershed in Nepal - Lamichhane, Babu Ram; Awasthi, Keshav Datt (Journal of Forest and Livelihood, 2009)
Nepal, as a part of the earth, cannot remain untouched by the global climate change. This study identifies the indicators of changing climate at local level, particularly at sub-watershed in the mid-hills of Nepal. It shows that considerable warming has occurred in the study area. The average temperature has risen by 1.5 °C from 21.6 °C during 1978-82 to 23.1 °C during 2001-06. Annual rainfall is fluctuating; prolonged dry periods and short but intense rainfall during rainy season are being observed in recent years. The study also identifies non-climatic indicators of warming climate observed in the study area such as increase in insects and pests, spread of invasive species at higher elevations, change in flowering time and change in time of harvest etc. Key words: climate warming, climate change indicator, temperature, rainfall, insects and pests Full text is available at the ForestAction website Journal of Forest and Livelihood 8(1) February 2009 pp.99-105